Reliability assessment of ultimate and serviceability limit states of underground rock caverns - Wong, J. Y. K. (2012)
Both the stress-induced and structurally controlled instabilities are investigated by means of the Distinct Element program UDEC. The Factor of Safety is used as the criterion for the Ultimate Limit State and the volume of rock mass displaced into the cavern was adopted as the Serviceability Limit State criterion. Numerical experimentations are performed in accordance with the methodology of 2k factorial design, from which two polynomial regression models are developed for reliability analysis. The First Order Reliability Method (FORM) was used to determine the probability of failure for the limit states.